2007
DOI: 10.1093/nar/gkm752
|View full text |Cite
|
Sign up to set email alerts
|

Real-time measurements of the nucleation, growth and dissociation of single Rad51–DNA nucleoprotein filaments

Abstract: Human Rad51 (hRad51), the protein central to DNA pairing and strand exchange during homologous recombination, polymerizes on DNA to form nucleoprotein filaments. By making use of magnetic tweezers to manipulate individual DNA molecules, we measured the nucleation and growth of hRad51 nucleoprotein filaments, and their subsequent disassembly in real time. The dependence of the initial polymerization rate upon the concentration of hRad51 suggests that the rate-limiting step is the formation of a nucleus involvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
90
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(104 citation statements)
references
References 55 publications
11
90
2
Order By: Relevance
“…We observed that the polymerization of hRad51 on dsDNA requires a minimal concentration of approximately 100 nM to initiate. This is consistent with previous results independently obtained both with conventional MT (20) and in single-molecule videomicroscopy (21) confirming the existence of a threshold concentration for hRad51 polymerization initiation. The threshold in ref.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…We observed that the polymerization of hRad51 on dsDNA requires a minimal concentration of approximately 100 nM to initiate. This is consistent with previous results independently obtained both with conventional MT (20) and in single-molecule videomicroscopy (21) confirming the existence of a threshold concentration for hRad51 polymerization initiation. The threshold in ref.…”
Section: Discussionsupporting
confidence: 93%
“…This contrasts with our previous report (20) in which the magnetic bead was blocked in torsion by the MT and the DNA molecule untwisted manually. We attribute this behavior to the viscous drag of the bead, which opposes the formation of the nucleoprotein filament and becomes the limiting factor at high hRad51 concentrations.…”
Section: Polymerization Initiation and Extension As A Function Of Concontrasting
confidence: 90%
See 3 more Smart Citations